2011
DOI: 10.1007/s00066-011-2186-x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Low Single Dose Cisplatin-based Concurrent Radiochemotherapy of Oral Cavity and Oropharynx Carcinoma

Abstract: Patients with ECS have an increased risk of distant metastases. Adjuvant low single dose cisplatin-based concurrent chemotherapy seems to have no influence on occult microscopic systemic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…1 ECS is correlated with increased rates of recurrence, contralateral recurrence, occurrence in unusual sites, and distant metastasis. 26 ECS is identified in up to 50% of neck dissection specimens and in approximately 20% of patients with HNSCC who have clinically negative neck examinations. 7 The current standard for the identification of ECS in patients with HNSCC is histopathological examination of neck dissection specimens.…”
Section: Introductionmentioning
confidence: 99%
“…1 ECS is correlated with increased rates of recurrence, contralateral recurrence, occurrence in unusual sites, and distant metastasis. 26 ECS is identified in up to 50% of neck dissection specimens and in approximately 20% of patients with HNSCC who have clinically negative neck examinations. 7 The current standard for the identification of ECS in patients with HNSCC is histopathological examination of neck dissection specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical lymph node metastasis is the single most important prognostic factor for pa-tients with oral cavity SCC, and accurately evaluating cervical lymph node metastases is critical for surgical and adjuvant therapy planning. Additionally, ENE-defined as extension of the metastatic tumor through the lymph node capsule into the surrounding connective tissue-is a known independent risk factor for the development of recurrence and distant metastases [16][17][18]. Wreesmann et al [3] and Myers et al [19] reported that patients with tongue cancer and ENE showed poor survival outcomes, with higher rates of regional recurrence and distant metastases than patients with positive cervical lymph nodes without ENE.…”
Section: Discussionmentioning
confidence: 99%
“…ECS is associated with decreased 5‐year disease‐specific survival to approximately 40%, compared to 70% among those without ECS . Moreover, ECS is an independent risk factor for the development of contralateral recurrence, recurrence in an unusual location, and distant metastases . Finally, a comparative analysis of patients with advanced‐stage head and neck cancers demonstrated that those patients with ECS were most likely to benefit from the addition of chemotherapy to adjuvant radiation …”
Section: Introductionmentioning
confidence: 99%